Pendampingan Pembelajaran Tulisan Arab dasar bagi Santri Program Takhassus di PGAI Padang - Iwan, Ediwan; Kustati, Martin; Gusmirawati, Gusmirawati (Jurnal Pengabdian Masyarakat, 2025)
The ability to write Arabic letters is a very important basic skill for students, especially in the PGAI Padang Special Education Program, as a foundation for understanding the Qur'an, yellow books, and various other Islamic literature. However, some students still experience difficulties in writing Arabic letters correctly and systematically. Based on these conditions, mentoring activities were carried out with the aim of improving basic Arabic writing skills through a service learning approach, where the learning process is combined with real experience and reflection. The mentoring steps include initial observation, implementation of pre-test and post-test, guided writing practice, learning reflection, and final evaluation. Mentoring is conducted directly through intensive interaction between mentors and students to ensure understanding of the forms, rules, and fluency in writing Arabic letters. The results show a significant improvement in students’ ability to write Arabic letters, both in terms of accuracy of letter forms, neatness of writing, and writing speed. In addition, students become more confident and motivated to practice Arabic writing skills outside classroom activities. The implications of this activity indicate that the mentoring model based on service learning is effective when applied to Arabic learning in Islamic educational institutions, as it is able to integrate cognitive, affective, and psychomotor aspects in a balanced manner.